Primary intradural neuroendocrine tumour of spine: a rare pathology - Gupta, Vipin K.; Latawa, Archit; Kalra, Gagan; Radotra, Bishan D. (International Surgery Journal, 2018)
Neuroendocrine tumour in central nervous system is a very rare pathology. We hereby report a primary intradural neuroendocrine tumour, second to the only other case reported in literature till now as per the best of our knowledge. The tumour was completely intradural, spanning across five segments in the lumbar spine and no primary tumour could be detected elsewhere in body. The patient underwent surgery followed by radiotherapy and showed symptomatic relief. This case report focusses on compiling the available literature on spinal carcinoids (both primary and metastatic) and discussing the relevant investigations and available treatment options for the same.